IC 9324 Diesels In Underground Mines: Measurement And Control Of Particulate Emissions - Staff (The National Institute for Occupational Safety and Health (NIOSH), 1992)
The goal of the U.S. Bureau of Mines diesel engine research program is to reduce exhaust emissions from diesel-powered equipment used in underground mines. This research has led to significant advances in aerosol measurement and to the development of more effective emission controls. This Information Circular contains reports of some of the presentations made at the Bureau's Information and Technology Transfer Seminar on Diesels in Underground Mines given in Minneapolis, MN, on September 29-30, 1992. The seminar emphasized the measurement and control of diesel particulate matter emissions. Topics covered include a discussion of the health issues associated with the use of diesel equipment underground, an overview of regulations, measurement techniques for diesel exhaust aerosol, levels of diesel exhaust pollutants found in mines, and modern emission controls. An appendix is included that contains a report describing the capabilities of the Bureau's diesel emissions research laboratory, two papers describing the effects of engine maintenance or: emissions, a paper describing the monitoring of carbon dioxide in mine air as an indicator of air quality, a glossary, and a list of abbreviations and acronyms.